PENGARUH PEMBERIAN BELIMBING DAN MENTIMUN TERHADAP PENDERITA HIPERTENSI DI DESA LAU KERSIK KECAMATAN GUNUNG SITEMBER KABUPATEN DAIRI - Herri Novita Br Tarigan; Prista Hotmarina Purba (Jurnal Penelitian Keperawatan Medik, 2019)
Hypertension is a disease that is not uncommon in the community, including the Bukit Lau Kersik village. People with hypertension often do not show long-term symptoms and can be life-threatening. However, one of the management of hypertension that can be used as non-pharmacological therapy is consuming starfruit juice and cucumber which is quite easy to find in the Bukit Lau Kersik village. This combination of juices contains potassium which can reduce blood pressure in patients with hypertension. This study used Equivalent Time Sample Design with 14 subjects with hypertension in the Bukit Lau Kersik Village, Gunung Sitember Subdistrict, Dairi District. The technique of this research sample used Non-Probability Sampling with Saturated Sampling. The instrument used was a sphygmomanometer and a stethoscope. Bivariate data analysis in this study was the Wilcoxon statistical test. Based on the data analysis performed, the value of p is 0.011 < 0.05 was obtained, meaning that there was a significant relationship between giving star fruit juice and cucumber to hypertensive patients. Then it can be concluded that there is an influence between giving star fruit and cucumber juice to blood pressure reduction in hypertensive patients in Bukit Lau Kersik Village Gunung Sitember Subdistrict, Dairi District in 2019. Suggestion: The factors that affect blood pressure in hypertensive patients and checking blood pressure before drinking star fruit juice and cucumber.